Exploring the Tik-tok Application as a Learning Tool Impact Students' Writing Skill at Senior High School - Rifka Alwasi; Murni Mahmud; Geminastiti Sakkir (International Journal of Language, Education, and Literature, 2024)
At this time, Indonesia has entered an era of more profound digital transformation with various trends and changes occurring. As digital technology has advanced, social media has evolved into multiple platforms and activities that can be accessed. TikTok is one of the most famous social media platforms that target younger people, such as students, to share their videos. In addition, TikTok is also used for creative education, namely as a learning tool. Furthermore, the research objective is to explore the TikTok application as a learning tool that impacts students' writing skills. A qualitative method with a descriptive approach was employed. The result of this research showed that the TikTok application as a learning tool positively impacted students' writing skills first in psychology, namely increasing students' motivation, eliminating students' fear and shyness, and relieving students' anxiety in writing a text. The second is linguistics, which includes improving sentence structure, grammar, and vocabulary acquisition. The last is cognitive, such as students noticing the use of punctuation and capitalization and paying attention to spelling when writing a text.